2021
DOI: 10.1017/s1537592721002188
|View full text |Cite
|
Sign up to set email alerts
|

Economic Inequality and Political Responsiveness: A Systematic Review

Abstract: Do political outcomes respond more strongly to the preferences of the rich? In an age of rising inequality, this question has become increasingly salient. Yet, although an influential literature has emerged, no systematic account exists either of the severity of differentials in political responsiveness, the potential drivers of those differentials, or the variation across democracies. This article fills that gap. We analyze 1,163 estimates of responsiveness from 25 studies and find that, although this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…However, the effects of affluence have been rarely considered within this research. This is surprising given the fact that the research on unequal democracy has demonstrated that policy preferences differ depending on the income of citizens and that political decisions are biased towards the preferences of the affluent (Bartels 2008;Gilens 2012;Elkjaer and Klitgaard 2021;Elsässer, Hense, and Schäfer 2021). Based on this argumentation and the empirical findings, we expect differences in the preferences for democratic representation depending on the affluence.…”
Section: Wealth As Determinant Of Preferences For Democratic Represen...mentioning
confidence: 85%
See 1 more Smart Citation
“…However, the effects of affluence have been rarely considered within this research. This is surprising given the fact that the research on unequal democracy has demonstrated that policy preferences differ depending on the income of citizens and that political decisions are biased towards the preferences of the affluent (Bartels 2008;Gilens 2012;Elkjaer and Klitgaard 2021;Elsässer, Hense, and Schäfer 2021). Based on this argumentation and the empirical findings, we expect differences in the preferences for democratic representation depending on the affluence.…”
Section: Wealth As Determinant Of Preferences For Democratic Represen...mentioning
confidence: 85%
“…Further, and presumably partially as a result of the biased participation and selection, legislators' "responsiveness is strongly tilted toward the most affluent citizens" (Gilens 2012) and political outcomes correspond more strongly to the preferences of the rich than the poor (e.g. Bartels 2006;Elsässer, Hense, and Schäfer 2021;Elkjaer and Klitgaard 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Besides extending the geographical scope and documenting that unequal responsiveness exists in several rich democracies, some of these studies have focused on social groups beyond income, investigating representational inequality across educational groups (Schakel & van der Pas 2021) or occupation-based social classes (Elsässer et al 2021). Taken together, most responsiveness studies find a prorich bias in policymaking, in both economic and noneconomic policy domains (for recent meta-analysis, see Elkjaer & Klitgaard 2021). Less clear, however, remains the evidence on whether there are systematic differences across party families and whether inequality in responsiveness has increased over time (Mathisen et al 2021).…”
Section: Policy Responsiveness: Biased Decisions?mentioning
confidence: 99%
“…See Hopkin and Lynch (2016) for a discussion on Europe. See also Elkjaer and Klitgaard (2021) for a systematic review of the recent literature. 2.…”
Section: Introductionmentioning
confidence: 99%